2022
DOI: 10.1136/bmjopen-2021-059565
|View full text |Cite
|
Sign up to set email alerts
|

Costs of community-wide mass drug administration and school-based deworming for soil-transmitted helminths: evidence from a randomised controlled trial in Benin, India and Malawi

Abstract: ObjectivesCurrent guidelines for the control of soil-transmitted helminths (STH) recommend deworming children and other high-risk groups, primarily using school-based deworming (SBD) programmes. However, targeting individuals of all ages through community-wide mass drug administration (cMDA) may interrupt STH transmission in some settings. We compared the costs of cMDA to SBD to inform decision-making about future updates to STH policy.DesignWe conducted activity-based microcosting of cMDA and SBD for 2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…On the other hand, a cost survey which was part of a multi-country trial in India, Benin, and Malawi found that the cost per person was higher for MDA than for school-based targeted PC in India and Malawi but not in Benin. 10 However, this study also found that when “supportive” activities designed to optimise PC coverage were excluded, such as supervision from a non-governmental organisation, the cost per person was lower for MDA than for school-based targeted PC in all countries. 10 Real-world cost survey data and effectiveness data derived from experimental epidemiological studies are required to provide accurate evidence to determine if MDA is cost-effective compared to school-based targeted PC for STH control.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…On the other hand, a cost survey which was part of a multi-country trial in India, Benin, and Malawi found that the cost per person was higher for MDA than for school-based targeted PC in India and Malawi but not in Benin. 10 However, this study also found that when “supportive” activities designed to optimise PC coverage were excluded, such as supervision from a non-governmental organisation, the cost per person was lower for MDA than for school-based targeted PC in all countries. 10 Real-world cost survey data and effectiveness data derived from experimental epidemiological studies are required to provide accurate evidence to determine if MDA is cost-effective compared to school-based targeted PC for STH control.…”
Section: Introductionmentioning
confidence: 71%
“…Interviewer administered questionnaires were developed to collect information on cost, resource use, and time spent on the implementation of annual school-based targeted PC and MDA programs using albendazole (400 mg), which were assumed to be donated for school-age children and purchased for other population groups. Costs were categorised according to the components of PC implementation 7 , 10 , 19 : albendazole procurement (which includes its purchase, transport, and storage), training, community sensitisation, albendazole administration, and PC monitoring and evaluation ( Appendix p 2). The questionnaires were translated from English to Vietnamese and were pre-tested and revised with the research assistants who conducted the interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost-effectiveness of community-based MDA was due to economies of scale—as treatment programmes expand and treat more people there are administrative costs that are not reincurred or that max out and the incremental cost of treating another person decreases as more people are treated. Other studies 9 , 10 have shown that cost-effectiveness can be influenced by STH prevalence and consideration of costs for supportive activities such as advocacy campaigns.…”
mentioning
confidence: 99%
“…The cost of reaching an individual through a house-to-house drug distribution approach is, on average, five to ten times higher than that incurred by reaching a child through school distribution 5 , 6 , 7 in which the school is used as support infrastructure and the drugs are distributed within each class by teachers at minimal cost. 6 On the contrary, the house-to-house approach faces important costs due to the increased complexity of the activity and the need to recruit distributors.…”
mentioning
confidence: 99%